Hydrodynamic studies of floating structures: Comparison of wave-structure interaction modelling. (1st April 2022) - Sheng, W.; Tapoglou, E.; Ma, X.; Taylor, C.J.; Dorrell, R.M.; Parsons, D.R.; Aggidis, G.
Abstract: Current panel methods for wave-structure interactions employ the potential flow theory, which provide fast, reliable and relatively accurate predictions for the marine structures, and now some open source packages, NEMOH and HAMS, are available. In this research, the relative utility and performance of NEMOH and HAMS is compared with the well-known, state-of-art software, WAMIT. To bring focus to these comparisons, this research is based on three different floating structures: the truncated cylinder; the truncated cylinder with heave plate; and a novel multi-axis TALOS wave energy converter. To make the comparison more useful, this research investigates the incomplete and overlapped panels for the simple cylinder, to examine whether the respective code can handle these and still provide a meaningful solution. The comparisons may help us to understand whether the incomplete and/or overlapped panels can be used for simplifying the numerical modelling of those very complicated marine structures. From the comparisons, it can be seen the open source software, NEMOH and HAMS, both could produce very good results for the simple single marine structure, but also exhibit different capacities in dealing with more complicated marine structures. Specifically, HAMS could handle the thin structures and the overlapped panels effectively as WAMIT. Highlights: Discussion on the main issues in the panel methods. Comparisons of WAMIT, NEMOH and HAMS for three geometries, including TALOS WEC. The comparisons of the incomplete panels for the truncated cylinder. The comparisons of the overlapped panels for the truncated cylinder. The comparisons of capacities of open source software to WAMIT.